Pakistan : Staff Report for the 2015 Article IV Consultation, Ninth Review Under the Extended Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Request for Modification of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report, 2016)
This 2015 Article IV Consultation highlights that starting from a difficult position in 2013, Pakistan has made substantial progress in reducing near-term economic vulnerabilities. Economic growth gradually increased from 3.7 percent in FY2012/13 to 4.2 percent in FY2014/15. During the same period, efforts to reduce power subsidies and raise tax revenue have lowered the budget deficit from 8.4 to 5.4 percent of GDP, although part of this adjustment reflected clearance of quasi-fiscal liabilities in the energy sector in 2013. In the medium term, growth is expected to reach about 5.5 percent, and inflation is expected to gradually rebound to the State Bank of Pakistan's target of mid-single digits.